2020
DOI: 10.1002/chem.201905288
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Opportunities for Platinum Nanoparticles Encapsulated in Porous Liquids as Hydrogenation Catalysts

Abstract: The unusual combination of characteristics observed for porousl iquids, which are typicallya ssociatedw ith either porous solids or liquids, has led to considerablei nterest in this new class of materials. However,t hese porous liquids have so far only been investigated for their ability to separate ands tore gases.H erein, the catalytic capability of Pt nanoparticles encapsulated within aT ype Ip orousl iquid (Pt@HS-SiO 2 PL)i se xplored for the hydrogenation of several alkenesa nd nitroarenes under mild cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…After this initial evaluation, in another study, Maschmeyer et al investigated the catalytic capability of Pt@HS-SiO 2 PL for the hydrogenation of several alkenes and nitroarenes. [70] As expected, compared with Pt@HS-SiO 2 and OS-(Pt@HS-SiO 2 ), the most active catalyst for the hydrogenation of 1-decene is the Pt@HS-SiO 2 PL. Additionally, it was found that PLs could be recycled at least twice, confirming the recyclability and stability (Figure 23c).…”
Section: Catalytic Conversionsupporting
confidence: 62%
See 2 more Smart Citations
“…After this initial evaluation, in another study, Maschmeyer et al investigated the catalytic capability of Pt@HS-SiO 2 PL for the hydrogenation of several alkenes and nitroarenes. [70] As expected, compared with Pt@HS-SiO 2 and OS-(Pt@HS-SiO 2 ), the most active catalyst for the hydrogenation of 1-decene is the Pt@HS-SiO 2 PL. Additionally, it was found that PLs could be recycled at least twice, confirming the recyclability and stability (Figure 23c).…”
Section: Catalytic Conversionsupporting
confidence: 62%
“…(Reproduced with permission. [70] Copyright 2020, Wiley). d) Schematic illustration of the formation and stabilization of PdNPs in C 4 R COCs PL for photocatalytic hydrogen evolution.…”
Section: Chiral Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such pseudo-zeroorder reactions can be observed in certain concentration ranges at high reactant concentrations in heterogeneously catalysed reactions. 27 However, despite the slight deviations of the fitted concentration from the measured concentration profile, a first-order reaction can still be applied in the case of the hydrogenation carried out at 0.4 MPa. This is also confirmed by the fact that the k 0.40MPa /k 0.25MPa ratio of 1.61 corresponds very well with the calculated pressure ratio of 1.6.…”
Section: Carbon Fibre Catalystmentioning
confidence: 99%
“…Their modular nature and structure diversity facilitate the exquisite control over porous liquids with respect to the pore size and chemistry through the judicious selection of structural constituent. Such versatile porosities thereby enable systematic studies that afford an understanding of structure-function relationships of porous liquids, which has led them to be of particular interest for potential utility in gas storage [8][9][10][11][12][13][14][15][16] , separations [17][18][19][20] and catalysis [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%